1999
DOI: 10.1152/ajplung.1999.277.6.l1118
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait locus mapping of airway responsiveness to chromosomes 6 and 7 in inbred mice

Abstract: Quantitative trait locus (QTL) mapping was used to identify chromosomal regions contributing to airway hyperresponsiveness in mice. Airway responsiveness to methacholine was measured in A/J and C3H/HeJ parental strains as well as in progeny derived from crosses between these strains. QTL mapping of backcross [(A/J x C3H/HeJ) x C3H/HeJ] progeny (n = 137-227 informative mice for markers tested) revealed two significant linkages to loci on chromosomes 6 and 7. The QTL on chromosome 6 confirms the previous report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 21 publications
4
39
0
Order By: Relevance
“…However, both the A/J and C57BL/6J strains of the cross used to map the Aliq1 locus carry a null allele at the Par1 locus (Manenti et al, 1996), suggesting that the Aliq1 locus is distinct from the Par1 locus. On chromosome 6, the Bhr5 locus, controlling noninflammatory bronchial airway hyper-responsiveness, was mapped in a region proximal (50 cM) to that of the Pas1 locus (74 cM), indicating that these two loci are distinct (De Sanctis et al, 1999;Manenti et al, 1999). More recently, additional loci affecting lung inflammatory response have been mapped on chromosomes 9, 10, 15, and 18 (Malkinson et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, both the A/J and C57BL/6J strains of the cross used to map the Aliq1 locus carry a null allele at the Par1 locus (Manenti et al, 1996), suggesting that the Aliq1 locus is distinct from the Par1 locus. On chromosome 6, the Bhr5 locus, controlling noninflammatory bronchial airway hyper-responsiveness, was mapped in a region proximal (50 cM) to that of the Pas1 locus (74 cM), indicating that these two loci are distinct (De Sanctis et al, 1999;Manenti et al, 1999). More recently, additional loci affecting lung inflammatory response have been mapped on chromosomes 9, 10, 15, and 18 (Malkinson et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…After this hybridization step, the slides were incubated with fluoresceinated antidigoxigenin Ab and counterstained with 4,6-diamidino-2-phenylindole. The data obtained indicated that the mRasGRP4 gene resides at, or near, a site that controls baseline airway reactivity in backcrossed A/J and C3H/ HeJ mice (24). Thus, mBMMCs were generated from A/J and C3H/HeJ mice by culturing their bone marrow progenitors for 2-7 wk in IL-3-enriched medium in the presence or absence of c-kit ligand.…”
Section: Chromosomal Location Of the Mrasgrp4 Gene And Identificationmentioning
confidence: 99%
“…Many genes (e.g., those that encode IL-4, IL-5, IL-12, IL-13, IL-4R␣, TIM1, bradykinin, ADAM (a disintegrin and metalloprotease) member 33, Fc⑀RI␤, tryptase, leukotriene C 4 synthase, prostaglandin D 2 synthase, and complement 5) have been implicated in this airway disorder. De Sanctis et al (24) noted that baseline airway reactivity to methacholine in inbred C3H/HeJ and A/J mice is dominantly influenced by an unidentified gene on mouse chromosome 7B1 ϳ20 cM from the centromere. This site was not identified in backcrossed A/J and C57BL/6 mice (33).…”
Section: Location Of the Mrasgrp4 Gene At A Site On Chromosome 7 Thatmentioning
confidence: 99%
See 1 more Smart Citation
“…As respiratory pattern/function examination in the mouse by plethysmography yields results far more sensitive and informative than those other techniques can afford when betweenstrains comparison is the aim (17,19,41), we analyzed SeV resistance/susceptibility phenotypes during the first week after infection by simultaneously implementing double-chamber plethysmography, histological evaluation, and lung virus yield assaying techniques. Overall, this approach revealed a pattern of continuous variation, with resistant, intermediate, and susceptible strains, which would be suggestive of a complex trait controlled by several genes.…”
mentioning
confidence: 99%